2017
DOI: 10.1123/jab.2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Bipedal Stance Stability and Locomotor Stability Following a Trip in Unilateral Vestibulopathy

Abstract: Posturography is used to assess balance in clinical settings, but its relationship to gait stability is unclear. We assessed if dynamic gait stability is associated with standing balance in 12 patients with unilateral vestibulopathy. Participants were unexpectedly tripped during treadmill walking and the change in the margin of stability (MoS) and base of support (BoS) relative to nonperturbed walking was calculated for the perturbed and first recovery steps. The center of pressure (COP) path during 30-s stanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…However, as the majority of falls in older adults occurs during walking, stability control specifically while walking should be considered. It is important to note that stability control during static tasks shows little relationship with more dynamic and reactive tasks [12][13][14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, as the majority of falls in older adults occurs during walking, stability control specifically while walking should be considered. It is important to note that stability control during static tasks shows little relationship with more dynamic and reactive tasks [12][13][14].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…No studies are available evaluating the effect of a dynamic orthosis on gait and global sagittal alignment (GSA) of the spine 12,14,15. Data in previous studies regarding balance has mainly been retrieved during static tasks, such as standing, but it is important to note that stability control during static tasks shows little relationship with more dynamic tasks performed during activities of daily living 7,8,17…”
Section: Introductionmentioning
confidence: 99%
“…not older adults), or that reactive adaptation was not analysed in the studies. Cable trip systems, in conjunction with either treadmill or overground walking have been used effectively on multiple occasions to analyse gait stability and adaptation in multiple participant groups 3.1 (Süptitz et al, 2012, Senden et al, 2014, McCrum et al, 2016a, McCrum et al, 2017a. Another method for initiating tripping responses is the use of objects popping up from the ground, inhibiting the swing phase of gait (Pijnappels et al, 2005b, Pijnappels et al, 2005c.…”
Section: 1mentioning
confidence: 99%
“…a jump and land test). Regarding falls, standing balance tests in various forms have often been used to assess fall risk, but static and dynamic posturography outcomes could not distinguish previous older fallers from older non-fallers in one study (Baloh et al, 1994) and have repeatedly shown a lack of association with balance recovery performance during dynamic and reactive balance tasks (Owings et al, 2000, Mackey and Robinovitch, 2005, Bhatt et al, 2011, McCrum et al, 2017a.…”
Section: 221: Specificitymentioning
confidence: 99%
See 1 more Smart Citation